`Setting the benchmark` part 1: The contextualised physical demands of positional roles in the FIFA World Cup Qatar 2022 - Bradley, P. S. (Biology of Sport, 2024)
This study aimed to contextualise and benchmark the positional role demands during the FIFA World Cup Qatar 2022. With FIFA`s official approval, all sixty-four games were analysed during the competition (n=722) using a multi-camera computerised tracking system. During a typical FIFA World Cup Qatar 2022 match, defensive and central midfielders covered 8-19% more total distance than other positional roles (P<0.01; Effect Size [ES]: 0.8-2.5). The distances covered at higher intensities (=20 and =25 km · h-1) were 16-92% and 36-138% higher for wide midfielders and wide forwards compared to central defenders, defensive and central midfielders as well as centre forwards (P<0.01; ES: 0.7-2.2 and ES: 0.6-1.4). Defensive and central midfielders covered a greater proportion of their distance at higher intensities (=20 and =25 km · h-1) out-of-possession (71-83%; P<0.01; ES: 1.4-3.0), whilst attacking midfielders, wide and centre forwards more in-possession (55-68%; P<0.01; ES: 1.6-3.3). Nine out of the top ten sprint speeds attained at the tournament were from wide positional roles (35.3-35.7 km · h-1). All positional roles demonstrated a second half reduction in total distance covered compared to the first half (P<0.01; ES: 0.8-1.3). A decline between halves for the distances covered at higher intensities (=20 and =25 km · h-1) were more evident in attacking midfielders, wide defenders and midfielders than for other positional roles (P<0.01; ES: 0.3-0.7). Defensive midfielders and centre forwards were found to have the highest coefficient of variation (CV: 30.9-35.9% and 67.7-67.8%) for the distances covered at higher intensities (=20 and =25 km · h-1) compared to other positional roles. The current findings provide valuable contextual information about the contemporary positional demands of international football. This could be useful in the development and prescription of specific training regimes for national teams.